2023
DOI: 10.3390/pharmaceutics15072008
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin–Triterpene Type Hybrid as Effective Sonosensitizers for Sonodynamic Therapy in Oral Squamous Cell Carcinoma

Abstract: Sonodynamic therapy (SDT) is a non-invasive therapeutic modality in cancer treatment that combines low-intensity ultrasound (US) and sonosensitizers. Tumor cells are destroyed through the synergistic effects of ultrasound and a chemical sonosensitizer. This study focused on the synthesis and in vitro evaluation of the sonodynamic effect of natural curcumin, triterpene oleanolic acid, and their semi-synthetic derivatives on tongue cancer SCC-25 and hypopharyngeal FaDu cell lines. The combination of the tested c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…These findings indicated that the enhanced antitumour effect is attributed to the sonodynamic effect of the ultrasound in combination with the NSAIDs. Furthermore, our recent study showed that a curcumin–triterpene-type hybrid is an effective sonosensitiser for sonodynamic therapy in oral squamous cell carcinoma [ 33 ]. According to these results, in this study, we decided to conduct structural modifications by functionalising curcuminoid chalcones directly to obtain ester-type hybrid derivatives of curcuminoid chalcones.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings indicated that the enhanced antitumour effect is attributed to the sonodynamic effect of the ultrasound in combination with the NSAIDs. Furthermore, our recent study showed that a curcumin–triterpene-type hybrid is an effective sonosensitiser for sonodynamic therapy in oral squamous cell carcinoma [ 33 ]. According to these results, in this study, we decided to conduct structural modifications by functionalising curcuminoid chalcones directly to obtain ester-type hybrid derivatives of curcuminoid chalcones.…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature data [ 32 ] and biological results obtained in our study [ 33 , 35 ], we decided to select two curcuminoid chalcones also synthesised in previously reported work [ 35 ], a hybrid connection of curcuminoid chalcone and ibuprofen ( Figure 4 ). The compounds used for the sonodynamic study to evaluate anticancer activity were marked 1 , 2 , 3 , and 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation